2020
DOI: 10.1002/kjm2.12240
|View full text |Cite
|
Sign up to set email alerts
|

Treatment experience of Taiwanese patients with anti‐3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase myopathy

Abstract: Immune-mediated necrotizing myopathy (IMNM) has emerged as a new subgroup of idiopathic inflammatory myopathy in the past decade, associated with the presence of two autoantibodies against signal recognition particle and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR). We aim to analyze the clinical,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Among idiopathic inflammatory myopathies (IIM), immune-mediated necrotizing myopathy (IMNM) has been defined as a disease with proximal weakness, high CK level and histopathological changes including muscle fiber necrosis and regeneration with unremarkable inflammation [4,5]. Anti-HMGCR myopathy is a subgroup of IMNM and diagnosed high anti-HMGCR autoantibody level in addition to these clinical and muscle biopsy findings [1,4].Anti-HMGCR myopathy was first recognized in patients with statin exposure, but later has been determined also in statin-naive patients, particularly young adults and pediatric patients. Clinical spectrum has been expanded to typical classic type with acute/subacute progressive, proximal weakness and chronic limb-girdle muscular dystrophy (LGMD)-like phenotype [1,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among idiopathic inflammatory myopathies (IIM), immune-mediated necrotizing myopathy (IMNM) has been defined as a disease with proximal weakness, high CK level and histopathological changes including muscle fiber necrosis and regeneration with unremarkable inflammation [4,5]. Anti-HMGCR myopathy is a subgroup of IMNM and diagnosed high anti-HMGCR autoantibody level in addition to these clinical and muscle biopsy findings [1,4].Anti-HMGCR myopathy was first recognized in patients with statin exposure, but later has been determined also in statin-naive patients, particularly young adults and pediatric patients. Clinical spectrum has been expanded to typical classic type with acute/subacute progressive, proximal weakness and chronic limb-girdle muscular dystrophy (LGMD)-like phenotype [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…However, our patient had alleles HLA DRB1*08 and DRB1*15. Some reports suggest that the CK level can be utilized as a biomarker for disease activity in anti-HMGCR myopathy [1,4]. Remarkably, there are sufficient data that CK is an excellent marker of disease activity in anti-HMGCR, determining the level of muscle necrosis and being strongly correlated with levels of anti-HMGCR autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation can be achieved by de-termining myositis-specific antibodies ( 4), which we consider standard of care at our centre. While disease onset has been reported at any age, younger and statin-naive patients have an overall poorer treatment response and prognosis (14)(15)(16)26). Of particular importance is juvenile anti-HMGCRassociated IMNM with a recurrent and chronic disease course and a higher disease burden than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…They underwent muscle MRI, and it was found that adductors were earlier affected, while legs were relatively spared with the highest degree of involvement of the medial head of gastrocnemius. At the upper extremities, the biceps brachii was the most severely involved, followed by the triceps [ 71 ].…”
Section: Statins and Autoimmune Illnessesmentioning
confidence: 99%